Application of Capillary Electrophoresis in Drug Metabolism Studies - Jie Zhang; Jiri Konecny; Zdenek Glatz; Jos Hoogmartens; Ann Van Schepdael (Current Analytical Chemistry, 2007)
Capillary electrophoresis (CE) has been increasingly employed for the separation of pharmaceutical agents and drugs. This has arisen from the complementary mode of separation afforded by CE when compared to high performance liquid chromatography (HPLC). Qualities of CE such as high efficiency of separation, short analysis time, remarkably low injection volume and a variety of detection systems have facilitated acceptance of this technology. Since different drug metabolite enantiomers are formed in many metabolic pathways, the other indispensable advantage of CE over HPLC is the possibility of chiral separation without the need of special expensive columns. Recent advances in automated systems have made CE even more popular. The focus of this paper is to review recent studies and advances (mainly from 2000) of drug metabolism by using CE. The review is divided into two parts: (i) principles of CE separation of drugs and their metabolites and (ii) application of CE in drug metabolism studies. The first part introduces sample preparation, separation and detection modes involved in CE drug metabolism studies. To provide a deeper insight into the achievements, distinction between drug metabolism analysis in vivo and in vitro is made in the second part. Reported methods are discussed and summarized.
Keywords: Review